Labor market tightness and individual wage growth: Evidence from Germany - Stephan Brunow; Stefanie Lösch; Ostap Okhrin (Journal for Labour Market Research, 2022)
It is often stated that certain occupations in Germany, because of "Demographic Change ", are dwindling, implying a labor shortage. We investigate the 10-year wage growth of young employees entering the labor market in different occupations. Our findings suggest that regional labor market tightness in occupational fields significantly explains wage growth. Individuals who start their careers in a tighter labor market enjoy higher wage growth than workers in more relaxed labor markets. We identify some occupational fields where the effect is especially strong, such as several engineering groups, IT occupations, technicians, and some commercial occupations. Interestingly, health-care occupations reveal a reverse relation.
Keywords: J31; J44; R23; 330; Labor shortages; Occupation-specific wage curve; Demographic change; Wage growth